BLOCKCHAIN TECHNOLOGY IN BUSINESS ADMINISTRATION: OPPORTUNITIES AND RISKS - Farikhul Muafiq (Penelitian dan Pengembangan Ilmu, 2025)
The rapid development of blockchain technology has attracted attention across various sectors due to the need for secure and transparent transactions. Despite increasing adoption, most studies focus on technical aspects, resulting in a lack of understanding of its impact on organizational performance and strategic decision-making. This study uses a narrative review of peer-reviewed literature from the past 10 years, analyzing blockchain applications, outcomes, risks, and opportunities. The findings indicate that blockchain improves operational efficiency, transparency, trust, and governance, while supporting rapid, data-driven strategic decision-making and business model innovation. Implementation challenges include cybersecurity, interoperability, scalability, organizational resistance, high costs, and regulatory ambiguity. Blockchain integration offers significant transformational potential but requires effective risk management, capability development, and change management strategies. This review fills this literature gap and provides guidance for further research and managerial practice.